The effects of parity and stage of gestation on whole body and maternal growth and feed efficiency of gestating sows - Thomas, Lori Lynn (Kansas State University, 2017)
A study was conducted on a commercial sow farm to determine the effects of parity and stage of gestation on growth and feed efficiency of gestating sows. These data were also used to model changes in composition of maternal weight gain and products of conceptus throughout gestation. Feed intake and BW were measured daily from d 5 to 112 of gestation for 712 females. From d 5 to 39 of gestation, ADFI was lowest for parity 3+ sows compared to the other periods of gestation. Parity 2 sows, although provided the same feed allowance, had greater ADFI during the first period than parity 3+ sows. Average daily gain was lowest and G:F was the poorest from d 5 to 39 for each parity group compared with d 40 to 109 of gestation. Parity 1 and 2 sow ADG increased following d 39 of gestation but decreased from d 75 to 109. Parity 3+ sow ADG increased in each subsequent period of gestation. Parity 1 sows had the greatest ADG and G:F in comparison to parity 2 and 3+ sows in each period of gestation. Energy available for maternal growth was estimated after accounting for the energy needed to meet the sow’s maintenance requirement and the energy required for the growth of the conceptus. Following d 39 of gestation, energy available for maternal growth decreased at the expense of maintenance and conceptus requirements in each subsequent period of gestation for each parity group. After accounting for the weight of the conceptus, maternal ADG decreased from d 39 to 74, and increased d 74 to 109 of gestation, regardless of parity. Maternal G:F was greatest for parity 1 sows in most gestation periods. In conclusion, parity and stage of gestation impact sow feed efficiency and maternal growth with parity 1 sows having the greatest weight gain and best feed efficiency.
Keywords: feed efficiency; gestation; sowselectronic sow feeder